Decision-making and preventive non-surgical therapy in the context of a European core curriculum in cariology - Bottenberg, P.; Ricketts, D.N.J.; van Loveren, C.; Rahiotis, C.; Schulte, A.G. (European Journal of Dental Education, 2011)
This paper is part of a series of papers towards a European Core Curriculum in Cariology for undergraduate dental students. The European Core Curriculum in Cariology is the outcome of a joint workshop of the European Organisation for Caries Research (ORCA) together with the Association for Dental Education in Europe (ADEE), which was held in Berlin from 27 to 30 June 2010. The present paper covers decision-making and non-surgical treatment. In particular, it will provide some background information on this part of the European core curriculum. The dentist, on graduation, must be competent at applying the principles of prevention of dental hard tissue disease processes (primary prevention) and progression when it has manifested itself (secondary prevention). The competences should apply in differing ways to patients of all ages. Goals of prevention should be clearly defined in order for outcomes to be evaluated, and a dentist should be competent at determining these outcomes. Although this concept is recognised by many academics and experts, clinical teaching, practice and health insurance coverage frequently emphasise surgical treatment. There are many reasons and obstacles that might account for this, and this paper suggests some reasons why this might be and makes suggestions for how these can be addressed in the future. One factor that is essential in the provision of a preventive, non-surgical approach is that of communication with the patient. However, this unfortunately takes less space in the dental curricula compared with technical skills aimed at restorative procedures; this weighting needs to be more equally balanced.